ANALISIS PEMBENTUKAN NOMINA DENGAN PENAMBAHAN SUFIKS DALAM BUKU NON FIKSI MEIN JOB, MEINE SPRACHE, MEIN LAND: WIE INTEGRATION GELINGT KARYA OMID NOURIPOUR - Setiawan; Maya Adha Kusuma Winangun; Putrasulung Baginda (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2017)
Nouns is one of the type of words in German, which can be observed from any aspects. In this study, nouns was observed based on its formation process, especially by derivation with suffix addition. In this process, the suffix influences the meaning of nouns that has been formed. Therefore, this study has two objectives, they are, 1) identifying the process of Nouns formation with the addition of suffixes, and 2) identifying the meaning of Nouns which is formed with certain suffixes. This study was analyzed by using analytic-descriptive method. The data were obtained from a nonfiction book by Omid Nouripour which entitles Mein Job, Meine Sprache, Mein Land: Wie Integration gelingt. It contains 71 nouns which are formed with the addition of suffixes. The suffixes are -er, -nis, -ung, -e, -schaft, -heit, -tum, -t, -chen, -in, -ist, -ant, -ismus, -ion, -ar, -anz and -ity. The results of this study indicates that the nouns formation with the addition of suffixes involves element from different type of words as a basic word, such as verba and adjectiva, and also from the same type of words, which is nouns. Almost all suffixes have special significance in the source, so that they influence the meaning of the new nouns. On the other hand, two suffixes, which have no special meaning, suffix -ung and -t, have also been found. According to the study, the author suggests for next researchers who want to get more understanding about nouns formation for examining by other methods, for example with prefix addition